Asymmetric Construction of Bispiro‐Cyclopropane‐Pyrazolones via a [2+1] Cyclization Reaction by Dipeptide‐Based Phosphonium Salt Catalysis. Issue 10 (7th April 2020) - Lu, Dongming; Liu, Xin; Wu, Jia‐Hong; Zhang, Song; Tan, Jian‐Ping; Yu, Xiaojun; Wang, Tianli
Abstract: We reported herein an efficient alternative for asymmetric synthesis of structurally complicated chiral bispiro‐cyclopropane‐pyrazolones via dipeptide‐based phosphonium salt catalyzed [2+1] cyclization of 2, 3‐dioxopyrrolidines and halogenated pyrazolones. With this catalytic asymmetric protocol, a broad range of bispiro heterocyclic compounds bearing a pyrazolone unit were prepared in high yields with excellent diastereo‐ and enatioselectivities. Of note, this transformation proceeds in a really short time under mild reaction conditions. Abstract :